Polycystic ovary syndrome hormonal pharmacotherapy - С. Б. Чечуга (Publishing House TRILIST, 2019)
Polycystic ovary syndrome (PCOS) is a diagnosis of exclusion and an important interdisciplinary problem. New recommendations for PCOS management were presented to the world in 2018. These recommendations have been developed by the CREPCOS (Australia), ESHRE, ASRM, and more than 30 other organizations. This document based on evidence-based medicine data and replaces previous recommendations for the PCOS management 2011. This article presents a translation of only one section of recommendations on the PCOS pharmacotherapy. It is also presents the results of the combined oral contraceptive Belara used for hyperandrogenic conditions. The advantages of chlormadinone acetate, as a part of this drug, are that this progestin is a derivative of natural progesterone, and it is the only progestin with antiandrogenic effects with no cumulative dose (i.e., chlormadinone acetate has long-term predicted effect). Belara has a minimal risk of thromboembolic complications among other combined oral contraceptives, even in risk groups. The clinical efficacy of Belara in acne, seborrhea, and hyperandrogeny has been confirmed in numerous studies. In women taking this drug, a free testosterone decreased to the physiological level. The drug safety is also noted for fat and carbohydrate metabolism, which is reflected in a decrease of visceral fat. Every day there is an increasing data on the approaches in the PCOS diagnosis, treatment and prevention, therefore the strategies will be changed in the near future; it is possible that the name of this state will change in the future. A thorough study of PCOS is the key to resolving issues related to metabolic syndrome, diabetes mellitus and intermediate-vascular diseases, i.e. conditions that directly affect the life duration and quality.